Hydrochemical and Isotopic Characterization of the Impact of Water Diversion on Water in Drainage Channels, Groundwater, and Lake Ulansuhai in China - Yifan Han (MDPI AG, 2021)
Lakes are important natural water reservoirs that connect other water bodies and play essential roles in water supply, ecological preservation, and climate regulation. Because of global climate change and human activities, many lakes worldwide are facing severe challenges, such as ecological degradation and reductions in their water storage, levels, surface areas, and quality. Water diversion into lakes is considered an effective measure to address these challenges and has attracted much attention. Water has been diverted into Lake Ulansuhai through drainage channels from the Yellow River since 2013. This shallow lake is located in arid northern China and is greatly affected by high salinity and eutrophication. The lake is the lowest area in the Hetao basin and is a sink for terrestrial water in this region. High salinity in lake water, drainage channels, and groundwater caused by NaCl is an ongoing problem; however, water diversion has played an important role in dilution. The main hydrochemical type in the lake water is Cl·HCO3–Na·Mg, while those in the drainage channels and the groundwater show more diversity because of spatial differences. The main source of water in the lake (52–60%) is that diverted through six drainage channels on the west bank, followed by meteoric precipitation (36–38%). Groundwater recharge to the lake is minimal (west bank: 2–7%, and east bank: 1–5%). Extensive evaporation occurs in the lake before the lake water is discharged into the Yellow River through a waste canal. The hydrochemical evolution and salinization of the lake are dominated by the six drainage channels, followed by evaporation from the lake surface. Thus, resolution of soil salinization in the Hetao irrigation area is key to addressing salinity issues in the lake. This study will be helpful for the planning of future water diversion and ecological restoration.